Extracellular Trap‐Mimicking DNA‐Histone Mesostructures Synergistically Activate Dendritic Cells. Issue 22 (15th October 2019) - Weerappuli, Priyan D.; Louttit, Cameron; Kojima, Taisuke; Brennan, Luke; Yalavarthi, Srilakshmi; Xu, Yao; Ochyl, Lukasz J.; Maeda, Midori L.; Kim, Hong Sun; Knight, Jason S.; Takayama, Shuichi; Moon, James J.
Abstract: Extracellular traps (ETs), such as neutrophil extracellular traps, are a physical mesh deployed by immune cells to entrap and constrain pathogens. ETs are immunogenic structures composed of DNA, histones, and an array of variable protein and peptide components. While much attention has been paid to the multifaceted function of these structures, mechanistic studies of ETs remain challenging due to their heterogeneity and complexity. Here, a novel DNA‐histone mesostructure (DHM) formed by complexation of DNA and histones into a fibrous mesh is reported. DHMs mirror the DNA‐histone structural frame of ETs and offer a facile platform for cell culture studies. It is shown that DHMs are potent activators of dendritic cells and identify both the methylation state of DHMs and physical interaction between dendritic cells and DHMs as key tuning switches for immune stimulation. Overall, the DHM platform provides a new opportunity to study the role of ETs in immune activation and pathophysiology. Abstract : A novel DNA‐histone mesostructure (DHM) platform is reported, which mirrors the morphology of extracellular traps (ETs). This platform enables bottom‐up cell‐based assays to determine the role of the DNA‐histone substructure in ET‐associated phenomena. Here, DHMs are used to investigate ET‐mediated immunostimulation.